Avaliação da toxicidade da cromomicina A5 sobre o desenvolvimento in vitro de folículos pré-antrais em tecido ovariano ovino - Barros, Anna Cristinna Albuquerque (2024)
The aim of this study was to evaluate the effect of chromomycin A5 (CA5), a metabolite isolated from marine bacteria of the genus Streptomyces with potent antibacterial and antitumor activity, on the survival, activation and in vitro development of sheep preantral ovarian follicles. Ovarian cortex fragments collected from a slaughterhouse were randomly assigned to the following experimental conditions: uncultured control (NC), cultured in vitro (CIV) in α-MEM+ medium alone (MEM+); or with the addition of 0.3 µg/mL doxorubicin (DOX) as a positive control; or 100, 200 or 300nM of CA5 (CA5100, CA5200 and CA5300). After 1 or 6 days of IVC, the fragments were processed and stained with Periodic Acid Schiff (PAS) for morphological evaluation or Sudan Black B (SBB) to assess lipofuscin accumulation, immunohistochemistry for PCNA and TUNEL and gene expression for the FOXL2, BAX, BCL2 and caspase-3 genes. The CA5300 treatment showed the lowest follicle survival rate on D1 when compared to the other treatments (P<0.05). After 6 days of IVC, DOX, CA5200 and CA5300 significantly reduced survival in all follicular categories when compared to MEM+. With regard to normal primordial follicles, only MEM+ and CA5100 remained similar to NC after 1 day of IVC. With regard to follicular development, CA5300 was the only one with the lowest rate of developing follicles compared to MEM+ on D1. On D6, CA5200 and CA5300 had the lowest rates of developing follicles compared to the other treatments (P<0.05). As for stromal density, at D6, CA5200 and CA5300 had reduced cell density compared to MEM+ (P<0.05), while CA5100 remained similar. On D6 of IVC, all treatments showed a significantly higher percentage of senescent cells (SB) compared to MEM+, but CA5300 showed the highest mark for DNA fragmentation compared to MEM+ (P<0.05). With regard to cell proliferation, all treatments showed a significant reduction compared to MEM+ (P<0.05). In addition, the results showed that the mRNA levels for the FOXL2 gene were significantly reduced in the treatments with DOX and CA5100. The relative mRNA level of BAX/BCL2 was higher in the DOX treatment (P<0.05). However, no significant differences were observed between treatments in relation to caspase-3 expression. The data from the present study indicate that CA5 has dose-dependent cytotoxic effects on preantral follicles, affecting both stromal cells and the survival and development of preantral follicles, suggesting an effect on the induction of cellular senescence.